Analisis Pembelajaran SKI Menggunakan Jigsaw di Kelas VII MTsN 6 Nganjuk - Dayu Feri Apriliansah; Romelah Romelah (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The author focuses on analyzing the Jigsaw learning method in class VII SKI subjects at MTsN 6 Nganjuk. This writing aims to analyze the implementation of learning using the Jigsaw method, how this method can have an effect on student interaction, student activity in learning, and the difference in receiving material in SKI subjects. This writing uses a qualitative method with a phenomenological approach. Information obtained from observations, then interviews, and analysis of learning outcomes. The results obtained from the Jigsaw method analysis had a very drastic effect on increasing student activity. They are more enthusiastic, active, and able to work together in groups. Then this method increases students' activeness and self-confidence when appearing in front of the class. Although there are advantages, this research identifies a problem, namely the limited time which can reduce the overall application of the method. Some students like learning in groups to interact and exchange knowledge with other friends. However, some students experience challenges in understanding the material and they do not feel comfortable when explaining the material in front of the class. The conclusion is that the Jigsaw learning method provides positive things to increase active student interaction, involvement and increase self-confidence in SKI learning. The implication of this research is the need for plans that are ready and supported by teachers that can help to successfully analyze the Jigsaw method in the context of SKI learning at MTs level.